Teaching Premodern Asian History through Material Culture - Yunxin Li (Education About Asia, 2026)
To students who grow up outside of Asia and do not speak Asian languages, Asian history may seem distant and intangible. Premodern Asian history may seem even more elusive and disconnected to world history. Based on my experience teaching undergraduate Asian history courses, this article discusses the opportunities that material culture provides for instructors teaching premodern Asian history at the undergraduate or secondary school levels. It introduces five ways in which material culture informs teaching about premodern Asia: Using archaeological findings as historical evidence; facilitating cross-cultural comparisons with material culture; exploring the materiality of objects; teaching social history with objects; challenging the supremacy of the written word. Each section offers examples and pedagogical resources that are accessible and applicable to the classroom.
Keywords: Permodern Asia; Material Culture; Archaeology; Maps; Paintings; Art